CONTESTED INTERPRETATIONS OF INDONESIA’S INTERNATIONAL LEADERSHIP IN THE FOREIGN POLICY OF PRESIDENT SUSILO BAMBANG YUDHOYONO AND JOKO WIDODO - Aleksius Jemadu; Floranesia Lantang (JAS (Journal of ASEAN Studies), 2021)
The research aimed to examine the Indonesia’s international leadership on foreign policy throughout the period of President Susilo Bambang Yudhoyono and President Joko Widodo, who have developed different conceptualizations of foreign policy. It ultimately affects the way each of them makes an interpretation of what Indonesia should do with its international leadership. The research built a solid and rich theoretical framework by consulting on previous research focusing on factors that affect the nature of international leadership especially regarding the role of the individual styles of a state leader. The research had two illustrations or brief case studies, namely, the promotion of democracy and human rights and the initiative of promoting the Indo-Pacific cooperation with a special emphasis on the period of President Joko Widodo. The research finds that he has changed the nature of Indonesia’s international leadership to make it fit into his domestic agenda. While President Susilo Bambang Yudhoyono tends to make Indonesia’s international leadership as an essential part of his rigorous effort to build a post-authoritarian identity for a democratic and stable nation, President Joko Widodo prefers to make his foreign policy serve the accomplishment of his domestic priorities. The research concludes that Indonesia’s international leadership is much contingent upon individual preferences of the presidents in both formulating their policies as well as the implementation. Moreover, the research comes up with constructive ideas which might be useful to strengthen Indonesia’s international leadership in the future.